lncRNA myocardial infarction-associated transcript (MIAT) knockdown alleviates LPS-induced chondrocytes inflammatory injury via regulating miR-488-3p/sex determining region Y-related HMG-box 11 (SOX11) axis - Pan Weiwei (De Gruyter, 2021)
Long noncoding RNA (lncRNA) has been shown to be involved in the development of osteoarthritis (OA), an age-related bone and joint disease. However, the function and possible molecular mechanism of lncRNA myocardial infarction-associated transcript (MIAT) in lipopolysaccharide (LPS)-induced chondrocytes injury model remain unexplored. Cell viability and apoptosis were detected by methyl thiazolyl tetrazolium (MTT) and flow cytometry, respectively. Western blot was used to detect protein expression. The concentrations of inflammatory factors were estimated by enzyme-linked immunosorbent assay (ELISA). Abundances of MIAT, microRNA-488-3p (miR-488-3p), and sex determining region Y-related HMG-box 11 (SOX11) were examined by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR). Dual-luciferase reporter and RNA immunoprecipitation (RIP) assays were performed to analyze the interaction between miR-488-3p and MIAT or SOX11. LPS caused chondrocytes injury by reducing cell activity and increasing apoptosis rate and inflammatory factor secretions. Higher levels of MIAT and SOX11 and lower miR-488-3p were observed in LPS-treated C28/I2 cells. Importantly, knockdown of MIAT attenuated the LPS-induced cell injury by targeting miR-488-3p, and miR-488-3p overexpression weakened the LPS-induced cell injury by targeting SOX11. Additionally, repression of MIAT inactivated the LPS-induced NF-κB signaling pathway by decreasing SOX11 and increasing miR-488-3p. Knockdown of MIAT alleviated the LPS-induced chondrocytes injury by inhibiting the NF-κB signaling pathway mediated by the miR-488-3p/SOX11 axis.